CLASSIC-TPACK PDP for Teaching Composition: A Suggested Professional Developmental Program for Teaching L2 Writers - AlKadi, Sundus Ziyad (Journal of Education and Training, 2024)
This study explores Saudi foundation-year students’ instructional challenges in developing academic writing skills. Many students enter university with limited experience in writing, often relying on memorization rather than original expression, which leads to increased writing anxiety, hinders critical thinking, and places undue focus on error correction over fluency. To address these issues, the current paper introduces the CLASSIC-TPACK Professional Development Program (PDP) designed to enhance English instructors’ teaching methods. Rooted in The Critical Approach and Reid’s Teacher Training Quadrants, this flexible and inclusive framework supports varied learner needs. The program uses the Cooperative/Collegial Development Model to foster a collaborative environment where educators engage in reflective practice and action research, incorporating technology to enrich their teaching. This initiative aims to support the growth of skilled L2 writers and highlights the importance of ongoing professional development to strengthen academic writing within Saudi education.